Enhancing biohydrogen production from sugar industry wastewater using metal oxide/graphene nanocomposite catalysts in microbial electrolysis cell. (6th March 2020) - Jayabalan, Tamilmani; Matheswaran, Manickam; Preethi, V.; Naina Mohamed, Samsudeen
Abstract: Biohydrogen production through Microbial Electrolysis Cell (MEC) has drifted towards the development of suitable cost-effective cathode catalysts. In this study, two graphene hybrid metal oxide nanocomposites were used as catalysts to investigate hydrogen production in the MEC operated with sugar industry wastewater as substrate against phosphate buffer catholyte. Electrochemical characterizations exposed the better performance of NiO.rGO coated cathode which showed lesser overpotential at 600 mV and overall lowest resistance in the Nyquist plots than Ni-foam and Co3 O4 .rGO cathodes. The experimental results showed that at an applied voltage 1.0 V, NiO.rGO nanocomposite had exhibited maximum hydrogen production rate of 4.38 ± 0.11 mmol/L/D, Coloumbic efficiency of 65.6% and Cathodic hydrogen recovery of 20.8% respectively. The MEC performance in terms of biohydrogen production was 1.19 and 2.68 times higher than Co3 O4 .rGO and uncoated Ni-Foam. Hence, economical hybrid nanocomposite catalysts were demonstrated in MEC using industrial effluent for energy and environment sustainability. Graphical abstract: Image 1 Highlights: Hydrogen production in MEC was investigated using nanocomposites as cathode catalyst. Nanocomposites (NiO.rGO and Co3 O4 .rGO) were synthesized and coated on cathode surface. Characterizations revealed the higher activity of catalysts than bare Nickel foam. Synthesized catalysts enhanced the hydrogen production and coloumbic efficiency in MEC.